Effect of extrusion conditions and storage temperature on texture, colour and acidity of butter. (6th October 2016) - Kashaninejad, Morteza; Razavi, Seyed M A; Mazaheri Tehrani, Mostafa; Kashaninejad, Mahdi
Abstract : The effect of extruder shear rate (500, 750, 1125, 1500 and 1750/s), feed temperature (5, 7, 10, 13 and 15 °C) and storage temperature (5, 7, 10, 13 and 15 °C) on the acid value, colour (L*, a* and b*values) and texture (hardness and adhesiveness) of organic butter was examined. The optimised conditions in terms of extruder shear rate, feed temperature and storage temperature were 1345/s, 13 °C and 7 °C, respectively. At the optimised conditions; the predicted responses were determined as hardness 42.5 g/cm, work softening 67.2%, adhesiveness 42.5 gf/cm, acid value 3.4 mg KOH/kg and L* value 99.57.